Synthesis of 3-aryl-1-phosphinoimidazo[1, 5-a]pyridine ligands for use in Suzuki–Miyaura cross-coupling reactions. Issue 45 (23rd August 2021) - Tran, Ryan Q.; Dinh, Long P.; Jacoby, Seth A.; Harris, Nekoda W.; Swann, William A.; Williamson, Savannah N.; Semsey, Rebecca Y.; Yet, Larry
Abstract : 3-Aryl-1-phosphinoimidazo[1, 5- a ]pyridine ligands were synthesized from 2-aminomethylpyridine as the initial substrate via two complementary routes and were evaluated in the Suzuki–Miyaura cross-coupling reactions. Abstract : 3-Aryl-1-phosphinoimidazo[1, 5- a ]pyridine ligands were synthesized from 2-aminomethylpyridine as the initial substrate via two complementary routes. The first synthetic pathway underwent the coupling of 2-aminomethylpyridine with substituted benzoyl chlorides, followed by cyclization, iodination and palladium-catalyzed cross-coupling phosphination reactions sequence to give our phosphorus ligands. In the second route, 2-aminomethylpyridine was cyclized with aryl aldehydes, followed by the iodination and palladium-catalyzed cross-coupling phosphination reactions to yield our phosphorus ligands. The 3-aryl-1-phosphinoimidazo[1, 5- a ]pyridine ligands were evaluated in palladium-catalyzed sterically-hindered biaryl and heterobiaryl Suzuki–Miyaura cross-coupling reactions.